CHILDREN AND PLAY - Cabar, Huriye Demet; Altay, Merve; Altay, Birsen; Karaçuha, Melek Ersoy (Acta Scientiae et Intellectus, 2024)
It is aimed to give information about the child and play in this article by compiling the literature. In the article has been mentioned about play areas, the effects of play on children according to age groups, play and development and computer game dependency. As a result; the game is very important for the child, and nowadays the variety of games is increasing with technology.